Effect of Surface Pretreatment on Quality and Electrochemical Corrosion Properties of Manganese Phosphate on S355J2 HSLA Steel - Filip Pastorek (Coatings, 2016)
High strength low alloy (HSLA) steels exhibit many outstanding properties for industrial applications but suffer from unsatisfactory corrosion resistance in the presence of aggressive chlorides. Phosphate coatings are widely used on the surface of steels to improve their corrosion properties. This paper evaluates the effect of a manganese phosphate coating prepared after various mechanical surface treatments on the electrochemical corrosion characteristics of S355J2 steel in 0.1 M NaCl electrolyte simulating aggressive sea atmosphere. The manganese phosphate coating was created in a solution containing H3PO4, MnO2, dissolved low carbon steel wool, and demineralised H2O. Scanning electron microscopy (SEM) was used for surface morphology observation supported by energy-dispersive X-ray analysis (EDX). The electrochemical corrosion characteristics were assessed by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PD) measurements in the solution of 0.1 M NaCl. Method of equivalent circuits and Tafel-extrapolation were used for the analysis of the obtained results. Performed experiments and analysis showed that the morphological and corrosion properties of the surface with manganese phosphate are negatively influenced by sandblasting surface pretreatment.